THE BOT SYSTEM: THE PORTUGUSE CASE - Loforte, Francisco (Revista Ingeniería de Construcción, 2001)
The BOT model entails a concession company providing the finance, design, construction, operation, and maintenance of a privatised infrastructure project for a fixed period, at the end of which the project is transferred free of charge to the host government. In times of decreasing ability to raise funds for infrastructure projects, the BOT concept has been used by governments to implement privately financed construction projects. BOT mechanism offers increasing investment, construction, procurement, operation, and other business opportunities for private investors in infrastructure projects. However, under the BOT model, the responsibilities are heavy and stakes are high for both, governments and promoters. There are several constraints in successful implementation of BOT projects. This paper examines the use of BOT model and identifies major areas where BOT model is applied in Portugal by investigating theory and practice. It shows how BOT concept is used by central and local governments in implementing infrastructure projects in Portugal. It highlights the main constraints in successful implementation of BOT projects. Finally, it shows how government organisations assessed their BOT projects.